Pengaruh Content Marketing Tiktok terhadap Minat Beli @Somethincofficial Melalui Brand Awareness - Yunani, Akhmad; Kamilla, Zahra Nadira (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research was conducted to determine the effect of TikTok content marketing on buying interest at @somethincofficial through brand awareness. The purpose of doing this research is to find out and analyze how content marketing, buying interest, and brand awareness at @somethincofficial, the magnitude of the influence of brand awareness mediates TikTok content marketing on buying interest at @somethinkofficial. This research was conducted on Somethinc and TikTok users in Indonesia. The population size is not known using a non-probability sampling technique with purposive sampling. The sample of respondents was determined by the Cochran formula and a sample of 385 respondents was obtained. This study used a quantitative method with a descriptive analysis method and causal relationships using a path analysis model with data analysis using IBM SPSS Statistics 23 software. The results of the descriptive analysis in this study on the content marketing variable got a percentage of 83%, the purchase intention variable was 82%, and the brand awareness variable was 85%. The results of this study indicate that TikTok content marketing has a significant effect on purchase intention @somethincofficial, TikTok content marketing has a significant effect on brand awareness @somethincofficial, brand awareness has a significant effect on purchase intention @somethincofficial, brand awareness mediates TikTok content marketing on interested in buying @somethincofficial. Keywords: Content Marketing; Purchase Intention; Brand Awareness.